Assessment instruments for sustainability competences in applied biology: A systematic literature review - Rahardjanto, Abdulkadir; Husamah, Husamah; Lestari, Nurdiyah; Hadi, Samsun; Permana, Tutut Indria (Biology Education Department, Universitas Insan Budi Utomo, Malang, Indonesia, 2025)
Sustainability competences are essential for addressing complex global environmental, social, and economic challenges. However, tools to accurately assess these competences remain varied and underexplored, necessitating a comprehensive review of existing instruments. This study aims to systematically identify and analyze assessment instruments for sustainability competences through a systematic literature review (SLR). This type of research is a systematic literature review (SLR). The research instrument is an inclusion and exclusion criteria form. Using the Scopus database, articles published between 2010 and 2023 were screened based on inclusion criteria such as relevance to sustainability competences assessment, peer-reviewed status, and language (English). From an initial 234 articles, 11 met the criteria and were analyzed using bibliometric tools and qualitative synthesis guided by five research questions focusing on publication trends, subject areas, geographic distribution, keywords, and instrument characteristics. The results show dominance of Social Sciences in this field, with notable multidisciplinary inputs from Energy and Environmental Sciences. Key themes include teacher self-efficacy, institutional commitment, and educational tailoring, alongside challenges like weak theoretical foundations and limited curricular integration. The study concludes that culturally adapted and context-specific instruments are critical to effectively evaluate sustainability competences. It recommends further research to develop validated, comprehensive tools to support education and policy. This work provides a structured foundation for advancing sustainability competence assessment globally.